Transdisciplinary soil hydrology. Issue 1 (17th November 2020) - Hopmans, Jan W.
Abstract: In this paper, I present an evolutional pathway from disciplinary towards transdisciplinary science and research and offer contemporary examples of interdisciplinary research in soil hydrology. I further explore exciting opportunities that can lead to transdisciplinary research (TDres), as society demands for our science expertise to be increasingly involved in developing solutions in global issues of sustainability, food and water security, as well as in the decision‐making process. By way of TDres involvement in public policy, the scientist is going to be working in the trans‐science domains for which (s)he is likely not very prepared. Recommendations are presented to better train students and early‐career scientists so that they can be effective in participating in TDres and communicating their scientific knowledge to relevant stakeholders, the public, and decision makers as part of the policy‐making process. Core Ideas: A review of transdisciplinary science is presented. Opportunities in soil science and hydrology for transdisciplinary research are plentiful. There remain challenges for researchers to contribute to the science–policy interface.